Harmonization of Maternal Nutrition Trials – Finding and Creating Similarities in Protocols and Outcomes. (29th May 2020) - Gernand, Alison; Berhane, Yemane; Bhandari, Nita; Chowdhury, Ranadip; Jehan, Fyezah; Khatry, Subarna; Kolsteren, Patrick; Lee, Anne C C; Muhammad, Ameer; Shafiq, Yasir; Taneja, Sunita; Tielsch, James; et al.
Abstract: Objectives: Public health and clinical recommendations should be based on results from multiple studies, however trials often have outcomes that are not defined in the same way. This project aims to harmonize selected protocols, outcome definitions, and data analysis across five randomized trials of antenatal balanced energy-protein supplementation being conducted in Burkina Faso, Ethiopia, India, Nepal, and Pakistan. Methods: Harmonization efforts include a range of activities from reviewing detailed protocols, biospecimen collection plans, data dictionaries, and data analysis plans to proposing best practices and acceptable practices based on field limitations. Most studies have not begun or are early in enrollment, an ideal time frame to make changes. A two-day workshop of lead investigators, content experts and advisors will be held in late February, and harmonization activities will continue thereafter. Results: All studies are examining anthropometry at birth as a primary outcome, however the timing of birth measurements (hours since birth) and types of measurements taken differ across trials. All studies are estimating gestational age by ultrasound measurements, but the gestational age at ultrasound differs (in part due to differences in timing of antenatal care by country) as well as the number of fetal biometry measures. Finally, stillbirth is a key outcome across trials, but initial definitions had slight differences that will now be harmonized. We are also able to add new, important maternal and child health outcomes to each trial that will have the same protocols from inception (e.g., microbiome). Conclusions: Efforts thus far have resulted in communication between study investigators, consideration of improved protocols, and addition of new outcomes to collect across all sites. Further results are forthcoming after the February workshop, which will include documentation of how much definitions vary across studies and the challenges of standardization. We expect the harmonization process to improve overall reporting within each study and provide opportunities for better meta-analyses. Funding Sources: The Bill and Melinda Gates Foundation.